PACARAN DAN ZINA; Kajian Kekinian Perspektif al-Qurâ€™an - Himmah, Faiqoh (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2021)
Nowadays, it is not uncommon to see a pair of teenagers holding hands, making love, even kissing in public. Dating, that's the name. Regardless of age, both students, high school, junior high school, and even elementary school children have been directed there. As if this has become the culture of our nation. The reasons also vary, from introductions before heading to the household level to some just for fun. Then, what is the true Islamic view on this matter? In the discussion of this article, hopefully it will provide an understanding of adultery, so that they do not fall into promiscuity because in this advanced age of technology, actions that are prohibited by religion are often carried out by teenagers now because they are misusing existing facilities with negative activities. so they fall into free sex.